Cranberry proanthocyanidins inhibit the adherence properties of Candida albicans and cytokine secretion by oral epithelial cells - Feldman Mark; Tanabe Shinichi; Howell Amy; Grenier Daniel (BMC, 2012)
Abstract Background Oral candidiasis is a common fungal disease mainly caused by Candida albicans. The aim of this study was to investigate the effects of A-type cranberry proanthocyanidins (AC-PACs) on pathogenic properties of C. albicans as well as on the inflammatory response of oral epithelial cells induced by this oral pathogen. Methods Microplate dilution assays were performed to determine the effect of AC-PACs on C. albicans growth as well as biofilm formation stained with crystal violet. Adhesion of FITC-labeled C. albicans to oral epithelial cells and to acrylic resin disks was monitored by fluorometry. The effects of AC-PACs on C. albicans-induced cytokine secretion, nuclear factor-kappa B (NF-κB) p65 activation and kinase phosphorylation in oral epithelial cells were determined by immunological assays. Results Although AC-PACs did not affect growth of C. albicans, it prevented biofilm formation and reduced adherence of C. albicans to oral epithelial cells and saliva-coated acrylic resin discs. In addition, AC-PACs significantly decreased the secretion of IL-8 and IL-6 by oral epithelial cells stimulated with C. albicans. This anti-inflammatory effect was associated with reduced activation of NF-κB p65 and phosphorylation of specific signal intracellular kinases. Conclusion AC-PACs by affecting the adherence properties of C. albicans and attenuating the inflammatory response induced by this pathogen represent potential novel therapeutic agents for the prevention/treatment of oral candidiasis.